2017
DOI: 10.4049/jimmunol.1600568
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of CCR6+ and CXCR3+ Th Cell Migration in HIV-1 Infection Is Rescued by Modulating Actin Polymerization

Abstract: CD4+ T cell repopulation of the gut is rarely achieved in HIV-1–infected individuals who are receiving clinically effective antiretroviral therapy. Alterations in the integrity of the mucosal barrier have been indicated as a cause for chronic immune activation and disease progression. In this study, we present evidence that persistent immune activation causes impairment of lymphocytes to respond to chemotactic stimuli, thus preventing their trafficking from the blood stream to peripheral organs. CCR6+ and CXCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 62 publications
(59 reference statements)
1
42
0
Order By: Relevance
“…While effective antiretroviral therapy (ART) is able to restore the number of circulating CD4 + T‐cells, only a partial repopulation of Th17 cells is observed in the gut of the majority of treated patients, leading to a modest reduction in the levels of markers of chronic immune activation, thus inducing cell‐exhaustion and immune‐senescence . Increasing evidence support the idea that alterations in cell recruitment to the gut are a major obstacle for intestinal T‐cell reconstitution in HIV‐1 infected individuals, also in those under successful ART treatment . Mavigner and colleagues in 2012 demonstrated that T‐helper cells expressing the gut homing receptor CCR9 accumulate in the bloodstream of HIV‐infected individuals under ART, and proposed that the reduced expression of CCR9 agonist, CCL25, in the intestine prevents a proper recruitment of these cells into the tissues .…”
Section: Modulation Of Chemokine Activity During Hiv‐1 Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…While effective antiretroviral therapy (ART) is able to restore the number of circulating CD4 + T‐cells, only a partial repopulation of Th17 cells is observed in the gut of the majority of treated patients, leading to a modest reduction in the levels of markers of chronic immune activation, thus inducing cell‐exhaustion and immune‐senescence . Increasing evidence support the idea that alterations in cell recruitment to the gut are a major obstacle for intestinal T‐cell reconstitution in HIV‐1 infected individuals, also in those under successful ART treatment . Mavigner and colleagues in 2012 demonstrated that T‐helper cells expressing the gut homing receptor CCR9 accumulate in the bloodstream of HIV‐infected individuals under ART, and proposed that the reduced expression of CCR9 agonist, CCL25, in the intestine prevents a proper recruitment of these cells into the tissues .…”
Section: Modulation Of Chemokine Activity During Hiv‐1 Infectionmentioning
confidence: 99%
“…Mavigner and colleagues in 2012 demonstrated that T‐helper cells expressing the gut homing receptor CCR9 accumulate in the bloodstream of HIV‐infected individuals under ART, and proposed that the reduced expression of CCR9 agonist, CCL25, in the intestine prevents a proper recruitment of these cells into the tissues . On the contrary, is still debated if expression of CCL20 and CXCL10 is maintained or reduced in the intestine during the infection, probably due to the fact that the intestinal mucosa of different anatomical sites have been analyzed by the different groups. Recently, we have shown that T‐helper cells expressing the chemokine receptor CCR6 and CXCR3 accumulate in the blood of ART treated HIV‐1 infected patients and that their frequency correlates with markers of chronic immune activation .…”
Section: Modulation Of Chemokine Activity During Hiv‐1 Infectionmentioning
confidence: 99%
See 3 more Smart Citations